Qualidade física, química e físico-química de rúcula orgânica em função do período de colheita e armazenamento - Meinerz, Marta Juvênia Andrade Oliveira (Universidade Federal Rural do Semi-Árido, 2015)
The study aimed to determine the best harvesting period of organic arugula in the environmental conditions of potiguar semi-arid, from the qualitative aspects through analytical determinations of some physical and physico-chemical parameters. The experiment was conducted in a rural property Hortvida, which has the seal of certification by the International Organization Agriculture - OIA. After harvest the sauces were stored under refrigeration (12 ± 1 ° C and 75 ± 5% RH) in the laboratory of physiology and post-harvest technology UFERSA. We used a completely randomized design factorial (5x4), corresponding to five harvest periods (20, 24, 28, 32 and 36 days after transplantation) and four storage times (0, 4, 8 and 12 days) 04 repetitions, totaling 80 plots. Physical analyzes were performed, length and diameter of the business unit, number of leaves, weight loss; chemical and physicochemical: hydrogenic potential (pH), soluble solids (SS), titratable acidity (TA), ratio of ST / AT, vitamin C and chlorophyll. The results showed that refrigeration is an effective method to prolong the quality of organic arugula, with longer shelf life of about eight days; presenting better postharvest characteristics when harvested at 28 days after transplanting
Quality Physical, chemical and physicochemical organic arugula depending on the harvest and storage
Keywords: Rúcula; Hortvida - propriedade rural; Colheita e armazenamento - rúcula orgânica; Arugula; Hortivida - rural property; Harvesting and storage - organic arugula; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA